mtROS Induced via TLR-2-SOCE Signaling Plays Proapoptotic and Bactericidal Role in Mycobacterium fortuitum-Infected Head Kidney Macrophages of Clarias gariepinus - Dahiya, Priyanka; Hussain, Md. Arafat; Mazumder, Shibnath (Frontiers in Immunology, 2021)
The mechanisms underlying M. fortuitum-induced mycobacteriosis remain unexplored. Using headkidney macrophages (HKM) from Clarias gariepinus, we report that Ca2+ surge across mitochondrial-Ca2+ uniporter (MICU), and consequent mitochondrial ROS (mtROS) production is imperative for mycobactericidal activity. Inhibition of mtROS alleviated HKM apoptosis and enhanced bacterial survival. Based on RNAi and inhibitor studies, we demonstrate that the TLR-2-ER-stress-SOCE axis is instrumental for activating mt-Ca2+/mtROS cascade in M. fortuitum infected HKM. Additionally, pharmacological inhibition of mtROS attenuated the expression of CHOP, STIM1 and Orai1 which suggests a positive feedback loop between ER-stress-induced SOCE and mtROS production. Elevated TNF-α levels and caspase-8 activity were observed and our results implicate mtROS is crucial in activating the TNF-α mediated caspase-8 activation. Our results for the first time demonstrate mitochondria as an innate immune signaling center regulating mycobacteriosis in fish. We conclude, M. fortuitum-induced persistent SOCE signaling leads to mtROS production which in turn activates TNF-α/caspase-8 axis culminating in HKM apoptosis and bacterial clearance.